ANALISIS PENGELOLAAN DANA INFAQ MELALUI TATA KELOLA KEWIRAUSAHAAN MASJID - Tamimah; Sri Herianingrum; Nur Rachmat Arifin; Inayah Swasti Ratih (Ekonomi Islam, 2020)
Indonesia is one of the countries with the largest population in the world. There are tens of thousands of mosques in Indonesia. The preferred mosque is only a worship facility. If you remember in the time of the Prophet, the function of the mosque is not only as a place of worship but also as a social means such as the transfer of knowledge, problems of the Ummah, and so forth. One of the mosques is able to revitalize the mosque in the economic field by conducting fund management procedures with infaq. The method used used field research using descriptive qualitative methods, the primary data source used consisted of interviews with the general chairperson, mosque management, and the Baitul Hakam congregation mosque on Jalan Kalimas Baru No. 121 Perak Timur, Secondary data sources come from books, searches, internet, and articles that discuss this research. The results of the study showed that the infaq aid funds were used for promotional activities using mini markets, mineral water products, and making soy milk so that they needed sufficient funds for the mosque and support the community's needs. Keyword: Entrepreneurship Governance, Mosque, Infaq Funds